LED non-linearity mitigation in a NOMA-OFDM VLC system using a union of precoder and companding - Sharan, Nishant; Ghorai, Swapan Kumar; Kumar, Ajit (Optical and quantum electronics, 2022)
The power domain non-orthogonal multiple access (NOMA) has been considered as an outstanding candidate for 5G visible light communication networks. Due to the various salient features like robustness to multi-path fading, low latency, high compatibility with multiple input multiple output systems, etc. orthogonal frequency division multiplexing access (OFDM) is foreseen to exist in 5G systems. NOMA-based optical OFDM (O-OFDM) is expected to be a promising candidate for supporting high rate internet connectivity, especially for green indoor mobile networks. The OFDM waveform suffers from high PAPR issue. The high PAPR degrades the BER and also enhances the non-linearity in an O-OFDM system. In this paper, a hybrid technique using a blend of precoder with compander is implemented to reduce the PAPR of NOMA based DC-biased O-OFDM (DCO-OFDM) system. The proposed NOMA DCO-OFDM system exhibits a low PAPR of only 4.3 dB. Also, for a reference bit error rate of 10 - 4 , the proposed technique displays an error vector magnitude of 13.2 dB.